Afferent Projections to Area Prostriata of the Mouse - Hu, Jin-Meng; Chen, Chang-Hui; Chen, Sheng-Qiang; Ding, Song-Lin (Frontiers in Neuroanatomy, 2020)
Area prostriata plays important roles in fast detection and analysis of peripheral visual information. It remains uncle¬¬¬ar whether the prostriata directly receives and integrates information from other modalities. To gain insight into this issue we investigated brain-wide afferent projections to mouse prostriata. We find convergent projections to layer 1 of the prostriata from primary and association visual and auditory cortices, retrosplenial, lateral entorhinal and anterior cingulate cortices, subiculum, presubiculum and anterior thalamic nuclei. Innervation of layers 2-3 of the prostriata mainly originates from presubiculum (including postsubiculum) and anterior midline thalamic region. Layer 5 of the prostriata mainly receives its inputs from medial entorhinal, granular retrosplenial, medial orbitofrontal cortices and anteromedial thalamic nucleus while layer 6 gets its major inputs from ectorhinal, postrhinal and agranular retrosplenial cortices. Claustrum, locus coeruleus and basal forebrain provide relatively diffuse innervation to the prostriata. Moreover, Cre-dependent tracing in cortical areas reveals that the cells of origin of the prostriata inputs are located in layers 2-4 and 5 of the neocortical areas, layers 2 and 5 of the medial entorhinal cortex and layer 5 of the retrosplenial cortex. These results indicate that the prostriata is a unique region where primary and association visual and auditory inputs directly integrate with many limbic inputs.